Innovative evaluation of selinexor and JQ1 synergy in leukemia therapy via C-MYC inhibition - Pei-Hong Wang; Chu-Hong Hu; Jia-Qi Fan; Jia-Jun He; Ting-Fen Deng; Yan-Li Xu; Yu-Jun Dai; Shun-Qing Wang (Journal of Translational Medicine)
Abstract Background Acute myeloid leukemia (AML) remains a therapeutic challenge due to drug resistance and relapse. Selinexor, an XPO1 inhibitor, shows limited efficacy as monotherapy, necessitating combination strategies. JQ1, a BET inhibitor targeting MYC, may synergize with Selinexor to enhance antileukemic effects. Methods AML cell lines, primary patient samples, and xenograft models (MLL-AF9, CDX, PDX) were treated with Selinexor and JQ1 alone or combined. Synergy was assessed via viability assays (Compusyn/SynergyFinder), apoptosis (flow cytometry/Western blot), and C-MYC suppression (qPCR/CRISPR). In vivo efficacy was evaluated by tumor burden (flow cytometry) and survival. Results The combination demonstrated strong synergy (CI < 1, HSA > 10) across AML models, with > 80% inhibition in cell lines and primary samples. Mechanistically, it suppressed C-MYC (protein/mRNA), induced apoptosis (cleaved PARP), and arrested cell cycle. In vivo, the combination reduced leukemic burden in bone marrow, spleen, and liver, extending survival in xenografts. PDX models confirmed efficacy in primary AML cells. Conclusions Selinexor and JQ1 synergistically target AML by dual C-MYC inhibition, offering a promising strategy to overcome resistance. Further clinical evaluation is warranted.